EXPLOITED ADAMS’ EVE: ACHAKKA AND EKWEFI - Sharma, Anjali (International Journal of Research -GRANTHAALAYAH, 2025)
"One is not born a woman, rather becomes one". This ’becoming’ was a consequence, the end result of centuries long ’process’ that was a careful, cautious, planned, romantic exercise; a mental, social, biological, cultural, political conditioning enforced subtly yet sternly on the female gender. The web of ’constructs’, hierarchical order instructed, ensured and perpetuated her to be the ’object’ of meekness, docility and rendered her to be a powerless creature. The praxis included withholding, defining, limiting, and controlling her in the bounds as ’ghar ki lakshmi’, ’angel in the house’, ’Gruen e mban ndera e jo buka’, half doll-half angel’, ’Ҫ’e do mallnë eҫ’e do gjenë, and so forth, which got embedded as truths universally perpetuated. Slightest demurrals were pronounced blasphemous that were satanic, devilish in nature and hence, were ’made’, witches and whores. Hence, ’She’ has always been a sobriquet, an identity that was constructed, approved, appreciated, scrutinised and eroticised all by man, while women were mere acquiescing puppets.